Within tree distribution of a discoid gall on Caryocar brasiliense (Caryocaraceae) - DEMOLIN-LEITE, GERMANO LEÃO; DO NASCIMENTO, ALINE FONSECA; MARIA DE JESUS, FABIENE; MONTEZE-ALVES, SÉRGIO; FERNANDES, GERALDO WILSON (Revista Colombiana de Entomología, 2011)
We recorded the discoid gall spatial distribution within Caryocar brasiliense trees in two areas of pasture and one of savanna. A higher number of discoid gall/leaflet was observed in savanna than in the pastures. More discoid galls were found on the eastern slope trees followed by the northern slope trees while fewer galls were found on the foliage in the southern slope trees in savanna. However, in the pasture one, the lower discoid galls were observed on the eastern slope. More discoid galls were found on the leaves in the interior (leaves one and two) of the tree crown than at the border (leaves three and four), principally in the leaf position three in savanna. Leaf positions three and four supported 83.6% of all galls sampled. On the other hand, this insect changed its behavior in pasture one, attacking more the second leaf and, in this case, leaf positions three and four supported 32.8% of all galls sampled. More discoid galls were found on the median region compared to the distal and proximal longitudinal regions on leaflet in savanna and in pasture one. The discoid gall insect preferred colonized the central portion than the border portion or near mid vein on transversal regions on a leaflet in the pasture one. In the savanna, followed the same trend, but perhaps due to greater population, the discoid galls have spread more evenly by the leaf of the tree.